2010
DOI: 10.1097/inf.0b013e3181c37fb4
|View full text |Cite
|
Sign up to set email alerts
|

Automated Determination of Neutrophil Volume as Screening Test for Late-Onset Sepsis in Very Low Birth Infants

Abstract: W e read with interest the recent report by Haustein et al entitled "The likelihood of an indeterminate test result from a whole-blood interferon-␥ release assay for the diagnosis of Mycobacterium tuberculosis infection in children correlates with age and immune status." 1 This report adds to recent publications that question the performance of current interferon-␥ (IFN-␥) release assays (IGRA) for the diagnosis of tuberculosis (TB) in routine pediatric clinical practice. [2][3][4][5][6] The retrospective stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
50
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(54 citation statements)
references
References 3 publications
4
50
0
Order By: Relevance
“…These parameters can be measured by the VCS technology of the Coulter LH 780 hematology analyzer (9)(10)(11)(12)(13). This so-called VCS technology is analogous to microscopic evaluation of a peripheral blood smear but evaluates more than a microscope.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…These parameters can be measured by the VCS technology of the Coulter LH 780 hematology analyzer (9)(10)(11)(12)(13). This so-called VCS technology is analogous to microscopic evaluation of a peripheral blood smear but evaluates more than a microscope.…”
Section: Discussionmentioning
confidence: 99%
“…This study also gives additional information about effects of sepsis onset time and birth weight on VCS parameters. Previous studies mostly included adult patients and there was only one study including newborns to diagnose late-onset neonatal sepsis (11)(12)(13)(14). Raimondi et al (2010) reported the cutoff levels of MNV and VDW as 148 au and 27.5 au in late-onset sepsis of very-lowbirth-weight infants, including 20 with proven and 20 with clinical sepsis.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations